(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The absence of oil and gas in section of the Azat-1 well is connected with the following causes: 1) in the section of the Azat-1 well thick (up to 500 m) shale seals of lower oligocene (Shoragbjur suite) do not participate; 2) the very close occurrence and connection of paleocene-eocene sections, which are exposed in the Azat-1 well and in valey of the Azat River; 3) the existense of paleocene-middle eocene vertical and turned beds in the Azat-1 well and in outcrops of the Azat River basin; 4) the close neighbourhood of the Azat-1 well and Azat fault. Favorable conditions for accumulation and conservation of oil and gas may be expected in the paleogene-neogene sedimentary sections of area between vv. Nubarashen–Djrvej and of area of well Razdan-11.